OP20 The impact of modifiable early life risk factors for childhood adiposity: findings from the Southampton Women's Survey. (2nd September 2014) - Crozier, SR; Inskip, HM; Harvey, NC; Barton, BD; Godfrey, KM; Cooper, C; Robinson, SM
Abstract : Background: The prevalence of childhood obesity has risen in recent decades. Research into the causes has revealed several environmental factors that operate in early life, suggesting that this may be a critical period when appetite and regulation of energy balance are programmed. Potential early life risk factors include maternal obesity, excessive gestational weight gain, smoking in pregnancy, low maternal vitamin D status and short duration of breastfeeding. These risk factors may cluster together; insight into the potential impact of strategies to reduce childhood obesity could be gained by evaluating their combined effect. Methods: The Southampton Women's Survey has measured the diet, body composition, physical activity and social circumstances of 12, 583 non-pregnant women aged 20 to 34 years living in the city of Southampton, UK. Women who subsequently became pregnant were studied throughout the pregnancy, and their offspring have been assessed in infancy and childhood. A subset of children was invited for assessment of body composition using Dual-Energy X-ray Absorptiometry at ages 4 and 6 years. Fat mass, a direct measure of adiposity, was derived from the whole body scan. Obesity was also examined using body mass index (BMI) and International Obesity Task Force-defined overweight/obese. Risk factors considered were maternal BMI before pregnancy >30 kg/m 2, excess gestational weight gain according to Institute of Medicine guidelines, smoking in pregnancy, maternal late pregnancy vitamin D concentrations <64 nmol/L, and never or less than one month duration of breastfeeding. Results: Of 991 children with available data, 148 had no risk factors, 330 had one, 296 had two, 160 had three, 57 had four or five. After taking account of a number of confounding variables, there were clear, graded increases in all adiposity outcomes at ages 4 and 6 years with increasing number of risk factors. The relative risks of being overweight/obese for children with 4 or 5 risk factors compared to those with none were 3.99 (95% CI 1.83, 8.67) at age 4 years and 4.65 (95% CI 2.29, 9.43) at age 6 years. Conclusion: The associations between the risk factor score and all adiposity outcomes were strong. Intervention in early life may therefore be an effective preventative strategy to reduce childhood adiposity, with potential for subsequent benefits to adult health.